2017
DOI: 10.18632/oncotarget.15722
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetically altered miR-1247 functions as a tumor suppressor in pancreatic cancer

Abstract: Altered expression of microRNAs has been strongly implicated in human cancers, and growing evidence is emerging that a number of miRNAs are downregulated in cancer associated with CpG island hypermethylation. Although pancreatic cancer is one of the most malignant human cancers, the roles of miRNAs underlying the tumorigenesis of pancreatic cancer are still poorly understood. In the present study, we explored the molecular functional role of microRNA-1247 as tumor suppressor associated with epigenetic alterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
(37 reference statements)
0
22
0
Order By: Relevance
“…Studies on epigenetic regulation indicated that in the tumor progression, even in early stages, the promoters of DNA loci encoding tumor suppressor miRNAs invariably harbor hypermethylated CpG islands. 26 , 40 Interestingly, we noted that the promoter region of miR-106a-5p gene was notably hypermethylated in RCC tissues in contrast to normal adjacent tissues, or rather, the downregulation of miR-106a-5p in RCC was partly attributed to methylation. The miRNAs biogenesis commences with processing of primary miRNAs (pri-miRNAs), in which RNA binding protein DGCR8 and the ribonuclease type III DROSHA are intricately involved.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Studies on epigenetic regulation indicated that in the tumor progression, even in early stages, the promoters of DNA loci encoding tumor suppressor miRNAs invariably harbor hypermethylated CpG islands. 26 , 40 Interestingly, we noted that the promoter region of miR-106a-5p gene was notably hypermethylated in RCC tissues in contrast to normal adjacent tissues, or rather, the downregulation of miR-106a-5p in RCC was partly attributed to methylation. The miRNAs biogenesis commences with processing of primary miRNAs (pri-miRNAs), in which RNA binding protein DGCR8 and the ribonuclease type III DROSHA are intricately involved.…”
Section: Discussionmentioning
confidence: 87%
“…To further discuss the methylation condition of miR-106a-5p gene promoter region in vivo , three pairs of tissue samples (RCC tissues and normal adjacent tissues) from 30 pairs of RCC patients were randomly allotted for MS-PCR and the results revealed higher methylation and lower unmethylation levels in the 3 cases of tumor tissues versus normal adjacent tissues ( Figure 6b ). Yi, et al 26 reported that the downregulation of miRNA in tumor cell lines might be attributed to the high methylation level of its gene promoter region. To figure out the changes of miR-106a-5p expression levels under the condition of demethylation by 5-AzaDc for 5 days, qRT-PCR was performed and the results showed that miR-106a-5p levels were remarkably upregulated in both 786-O and ACHN cell lines ( Figure 6c ).…”
Section: Resultsmentioning
confidence: 99%
“…Two of the metastatic group-related miRNAs, hsa-miR-1247 and hsa-miR-592, have been previously described as upregulated in high-grade uveal melanoma, by Falzone et al [18]. These results are contrary to several other studies showing that they usually act as tumor suppressors in pancreatic, colorectal, prostate, breast, and other cancers [21][22][23][24][25][26]. Similar to our studies, the overexpression of hsa-miR-592 was also described in progression of renal cell carcinoma, colorectal carcinoma with unaffected mismatch repair mechanisms, and gastric cancer [27][28][29].…”
Section: Discussionmentioning
confidence: 91%
“…In pancreatic ductal adenocarcinoma (PDAC) were found hyper-methylated the miR-9-1 , miR-124 s, miR-192 , miR-615-5p , and miR-1247 , suggesting tumor suppressor roles in this type of cancer [ 58 , 59 , 60 , 61 , 62 ]. Differently from breast and other cancers, miR-200a and miR-200b were reported to be expressed and de-methylated in PDAC [ 63 ].…”
Section: Epigenetic Alterations Of Mirnas In Cancermentioning
confidence: 99%